The EFL TEACHERS’ CHALLENGES IN TEACHING LISTENING SKILLS AT ONE ISLAMIC SENIOR HIGH SCHOOL IN MUARO JAMBI - Robi Soma; Yorina An’guna Bansa, yorina (Universitas Muhammadiyah Muara Bungo, 2024)
ABSTRACT The purpose of this study was to describe the EFL teachers’ challenges in teaching listening skills in one Islamic senior high school in Muaro Jambi. The researchers used qualitative research design for this research by applying a case study approach. The researchers interviewed two teachers who teach English to describe the challenges in teaching listening skills. The results indicated that all teachers knew teaching listening was not easy.They encountered several challenges in doing it. The challenges include: (1) Students low response, all teachers interviewed revealed their challenges in students low response. (2) Lack of vocabulary, which means the difficulty in understandin words from the audio. (3) Different accent from the native speaker is a challenge for teachers in teaching listening.(4) Less motivated, students who lack motivation make their enthusiasm and listening skills decrease. (5) Preparing media and equipment, which frequently occurs to start teaching listening. (6) Noisy environment, noisy sounds from outside the room can disturb the focus of students in listening. Keywords: Challenges, listening skills, and EFL students